Paradigma Aqidah Akhlak dalam Meneguhkan Identitas Keislaman Mahasiswa di Era Globalisasi - Najamudin Najamudin; Dwi Muliati; Alya Octavia Safitri; Septiyani Septiyani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The globalization era presents considerable challenges to the development of Islamic identity among university students. Technological progress, intercultural interaction, and exposure to various ideologies significantly affect students’ values and moral orientations. This study aims to analyze the Aqidah Akhlak paradigm as a framework for reinforcing students’ Islamic identity within the global context. This research applies a qualitative method through library research by examining classical and contemporary Islamic educational literature as well as relevant scholarly works. The findings demonstrate that the Aqidah Akhlak paradigm, which combines solid theological belief (aqidah) with moral character development (akhlak), plays an essential role in cultivating spiritual strength, ethical consciousness, and social responsibility. The reinforcement of Islamic identity is not limited to religious rituals, but also includes the internalization of faith-based values and the consistent application of moral principles in academic and social environments. Therefore, a contextual and integrated approach to Aqidah Akhlak education is necessary to develop intellectually competent and ethically grounded Muslim students in the era of globalization.